PENGARUH MOTIVASI KARYAWAN TERHADAP PRODUKTIVITAS PERUSAHAAN TEKSTIL PT. UNGGULREJO WASONO DI PURWOREJO - Dedi Iskandar; Ida Betanursanti (Universitas Ahmad Dahlan Indonesia, 2013)
This study aims to examine the correlations between employee motivation include individual, psychology, and organization factor and productivity in textile company UnggulrejoWasono Ltd. in Purworejo. The method used in this study is a questionnaire involving 50 employees as respondents. Data processed with SPSS version 13. The equation used is three variables of line arregression and analisis of Varian (ANOVA) test. The results obtained that the relationship between productivity(Y) and motivation(X) which includes individual (X1). psychology (X2) and organization factor (X3) as follows: Y=-13.266+0.517X1+1.121X2+1.104X3. In this study assume that motivation only have three variables, they are individual 18.6%, psychology 40.9% and organization factor 40.3% influence to the productivity of company. The percent error7,6% and coefficient regression value is 86,6%. Keywords: Motivation, individual factor, psychology factor, organization factor and productivity.